Science policy and national development - Sarabhai Vikram; Chowdhury Kamla (New Delhi Indian Council of Social Science Research, 2004)
The papers contained in this volume spell out some of the dreams that great scientist Vikram Sarabhai had for national development. He elaborates his dream in this book by talking about large nuclear power stations serving agro-industrial complexes of sy
Foreword by Indira Gandhi
Keywords: Science-research